Analysis Of Junior Savings Marketing Strategy At BSI KCP Surabaya Rungkut 1: Perspective Sharia Marketing - Ahmad Mubarroq Dawam; Fatkur Huda; Rukhul Amin (UNIVED Press, 2026)
This study aims to analyze the marketing strategy of the Junior Savings product at BSI KCP Surabaya Rungkut 1 from a sharia marketing perspective. This study primarily focuses on identifying the types and models of marketing strategies used and assessing the effectiveness of these approaches in attracting child customers. This study used qualitative methods by conducting in-depth interviews with individuals associated with BSI. The research findings indicate that BSI KCP Surabaya Rungkut 1 implements a marketing strategy through the 7P approach (Product, Price, Place, Promotion, People, Process, Physical Evidence) that aligns with sharia principles. This strategy includes collaboration with educational institutions, online promotions using text messages, involvement in children's events, and financial education presented in an engaging and educational manner. The use of the auto-debit feature and financial literacy activities from an early age are added value in fostering savings habits in children in accordance with Islamic teachings. Sharia marketing is reflected in an approach that emphasizes honesty, openness, trustworthiness, and blessings in every marketing step taken. Despite increasing public interest, challenges remain, such as limited digital access and a lack of public awareness of the importance of savings for children. Therefore, strengthening digital innovation, increasing financial literacy, and developing more flexible contracts are strategic steps to strengthen the marketing of Junior Savings in the future.